Association between Pre-operative Vitamin-D level and Shortterm Clinical Outcomes Regarding Pain & Disability following PLID surgery - Ashik Ahsan; Md Atikur Rahman; Md Motasimul Hasan; ABM Manwar Hossain; Mohammad Hossain (Bangladesh Journal of Neurosurgery, 2024)
Background: Low back pain (LBP) is a common problem affecting 70% of the population in the developed countries and prevalence is also increasing in the developing countries. There were strong associations between vitamin D deficiency and LBP. According to the latest report in Bangladesh 86% (eighty-six percent) people had hypovitaminosis- D. A high prevalence of vitamin D deficiency is seen in patients with degenerative diseases of the spine. Considering the hypovitaminosis D led to musculoskeletal issues we want to examine the level of vitamin D in patients before PLID surgery and observe its impact 01 month postoperatively regarding pain & disability outcomes by Visual Analogue Scale (VAS) & Oswestry Disability Index (ODI). Objectives: The objective of this study was to evaluate an association between preoperative Vitamin-D level and short-term outcome regarding pain & disability following PLID surgery. Materials and Methods: This cross-sectional observational study will be conducted in the Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University. Patient’s data will be collected in questionnaire/data collection sheet. All the patient will be evaluated by serum Vitamin-D level preoperatively. Patient will be clinically assessed by VAS (Visual Analogue Scale) score and ODI (Oswestry Disability Score) preoperatively and 01 month postoperatively. Then our aim is to determine a relationship between pre-operative Vitamin-D level and mean difference between pre and post-operative VAS & ODI Score. Statistical analysis: Data was processed and analyzed by using computer software SPSS (Statistical Package for Social Sciences) version 22. Appropriate statistical test for data analysis (Unpaired T-test) was done. Statistical significance was set at pvalue <0.05. Results: In this study population, the mean age was 42.84 ± 10.14 years ranging from 31 to 78 years. Out of 38 patients 17 (45%) patients had hypovitaminosis-D and 19 (55%) patient had normal vitamin-D level. 15 (39.5%), 11 (28.9%), 10 (26.3%) and 2 (5.3%) patients were service holder, housewife, Businessman and other (retired) respectively. T-test & Chi square test showed positive association between preoperative vitamin-D level and post-operative clinical outcome regarding pain and disability, with a significant p-value of p = <0.05. Conclusion: Our study has showed an association between Pre-operative Vitamin-D level and post-operative clinical outcome regarding pain & disability, that is, insufficient Vitamin-D level leads to decrease alleviation of symptoms following PLID surgery. Bang. J Neurosurgery 2024; 13(2): 75-85